Biomimetic Asymmetric Reduction Based on the Regenerable Coenzyme NAD(P)H Models - Chen, Mu-Wang; Wu, Bo; Liu, Zheng; Zhou, Yong-Gui (Accounts of chemical research, 2023)
Conspectus In nature, the coenzyme NAD(P)H is utilized for the transfer of hydrogen and electrons in biocatalytic reduction, which involves the process of recycling, coenzyme usage, and reduction. Inspired by the biological system, a series of nonregenerable achiral and chiral NAD(P)H models were synthesized and employed. However, this approach faced intractable limitations, such as the need for an equivalent amount of mimics, accompanied by the production of byproducts, which resulted in poor atom economy and difficult separation of products. Therefore, the development of new and efficient methodologies for synthesis, regeneration, and application of the NAD(P)H models in organic synthesis is greatly desired. To tackle these challenges, the regenerable achiral and chiral coenzyme NAD(P)H models were designed and synthesized based on the principles of biocatalytic reduction and applied them in biomimetic asymmetric reduction (BMAR) reactions. This Account summarizes our endeavors in rational design, synthesis, regeneration, and application of the NAD(P)H models. First, we will introduce the design and synthesis of regenerable and achiral coenzyme NAD(P)H models (dihydrophenanthridine and dihydropyrroloquinoxaline), which were successfully applied to BMAR of imines and heteroaromatics using homogeneous ruthenium complex as a regeneration catalyst, chiral phosphoric acid as a transfer catalyst, and hydrogen as the terminal reductant. Regenerable and achiral NAD(P)H models require the addition of chiral catalysts or chiral ligands for stereoselective control during the BMAR process. However, the screening of the chiral transfer catalysts is tedious. Narrow substrate scope further limited their application in organic synthesis. Therefore, we designed and synthesized regenerable and chiral NAD(P)H models (CYNAM and FENAM) with planar chirality, which were successfully applied in asymmetric reduction of imines and heteroaromatics using commercially available achiral Brønsted acids, Lewis acids, or organocatalysts as transfer catalysts and a homogeneous ruthenium complex as a regeneration catalyst. Notably, the original factor of enantioselective control is from the chiral NAD(P)H models. In addition, this strategy could also realize the asymmetric reduction of a myriad of electron-deficient tetrasubstituted alkenes, which are challenging substrates in transition metal catalyzed asymmetric hydrogenation. This methodology provides an efficient strategy for the synthesis of chiral building blocks and bioactive molecules. Finally, the detailed mechanism of BMAR, based on the regenerable NAD(P)H models, was elaborated through a combination of experiments and density functional theory calculations. In summary, we believe that the results presented in this Account hold significant implications beyond our work and have the potential for further applications in the field of biomimetic asymmetric catalysis and synthetic methodology.